Getting Started with Machine Learning in Game Development - Hakim, Taufiq Rahman; Muhammad Zaki, Dimas Aufa; Utami, Mirsanda Amelia; Syahri, Nur Alfi; Ardika, Sadin Yusuf; Risanty, Rita Dewi; Mujiastuti, Rully; Meilina, Popy; Amri, Nurul; Nurbaya, Sitti; Ardharani, Yana (Edumedia Solution, 2025)
The The webinar and workshop titled